Employee Performance: An Exploration Based on Leadership Style and Work Motivation in Large-Scale Companies - Firmansyah, Irman; Pitri, Tedi; Rijanto, Raden; Rifa'i, Asep Achmad (International Journal of Business, Law, and Education, 2026)
This study aims to explore employee performance in large-scale companies, focusing on the roles of leadership style and work motivation. Employee performance parameters are evaluated based on predictor variables of leadership style and work motivation, both individually and simultaneously. This research design uses a quantitative survey approach. A total of 34 research samples were selected using a total sampling technique approach. The main data source for this study is primary data collected from respondents' responses to the questionnaire. The data analysis methods include instrument validity and reliability tests, classical assumption tests, and descriptive statistics. In contrast, the influence test is carried out using correlation tests, the calculation and analysis of the Coefficient of determination (R2), and multiple linear regression models. The results of the study confirm that leadership style and work motivation can explain and predict employee performance variance in large-scale companies. Leadership style positively influences employee performance. Work motivation positively influences employee performance. However, work motivation has greater explanatory power than leadership style. Furthermore, the exploration of activity relationships indicates that leadership style and work motivation together positively influence employee performance in large-scale companies. This study comprehensively demonstrates that leadership style and work motivation are two important foundations that synergize in the human resource management (HRM) process to improve employee performance, and that this is applicable not only in large companies but also in HRM practices across companies of various sizes.